Talent retention: a case study at Malaysian Palm Oil Board (MPOB) / Wan Nur Syaza Dhaniyah Wan Mohd Khir Johari - Wan Mohd Khir Johari, Wan Nur Syaza Dhaniyah (2019)
This study is about talent retention in the Malaysian Palm Oil Board (MPOB). The aim of this study is to investigate the factors that contribute to talent retention at MPOB. The total of respondents is 220 from a different department at MPOB. The respondent was randomly selected from various races. The data was collected by using the quantitative method. There are four instruments in this study which are talent retention section that consist of 8 questions, leadership that consist of 7 questions, compensation section consists of 7 questions and job security section which consist 6 questions. The findings of this research showed that all the independent variables that were tested are significant. There is a relationship between job security, recognition, compensation, and leadership towards talent retention at MPOB. This research provides a guideline to improve and enhance talent retention for employers as it can strengthen talent retention in Malaysia.